Badania marketingowe rynków formalnych (na przykładzie giełd towarowych Unii Europejskiej) - Drewiński, Marek (Market Research of Formal Markets (on the Example of Commodities Markets in the European Union), 2006)
The paper is an attempt to describe some problems of market research applied in the process of investing on formal commodities markets. The methods of fundamental and technical analyses and the spheres of their application are presented and evaluated. The further part of the article is devoted to the possibility of adaptation of standard research methods of market transaction on Polish commodities markets. The final part shows the most important conditions of investors' behaviour taking the development perspectives of Polish commodities markets into account.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 331-340